Design and assessment of effective multimedia-based courseware for student quantitative data analysis - Yassin, Abdulnassir; Bashir, Ashadi; Surjono, Herman Dwi; Afdal, Zul; Novianto, Victor (International Journal of Evaluation and Research in Education (IJERE), 2025)
The rapidly evolving technological trends are transforming higher education. This study focused on designing and evaluating the effectiveness of multimedia-based courseware in improving students’ data analysis at Islamic University in Uganda. The objectives were: i) to create interactive multimedia courseware (IMC) to enhance students’ quantitative data analysis skills; ii) to evaluate the suitability of IMC’s content, interactivity, user interface, and design; and iii) to profile students’ perceived benefits of using the IMC to learn quantitative data analysis. A descriptive survey involving 160 education undergraduate finalists, selected through random and consensus sampling, was conducted. Data was collected through a self-report survey instrument with high validity (content validity index=0.886) and reliability (Cronbach alpha=0.878). The IMC development followed the analysis, design, development, implementation, and evaluation (ADDIE) model and Gagne’s learning events. Results indicated that the IMC content (mean=3.90, SD=0.94), interactivity (mean=4.10, SD=0.79), user interface (mean=4.04, SD=0.82), and screen design (mean=4.05, SD=0.87) were highly appropriate. Students perceived IMC as effective in enhancing their data analysis skills (mean=3.86, SD=0.92). The findings suggest that IMC can significantly improve students’ quantitative analysis abilities. However, recommending further studies on the impact of IMC on students’ quantitative data analysis skills comprehensively in a multidisciplinary manner, to potentially revolutionize learning.